Pengaruh Penggunaan Komunikasi Bahasa Besemah dan Keterlibatan Guru Terhadap Peningkatan Literasi Bahasa Pada Anak di TK Negeri Kota Pagar Alam - Fitriana, Eli (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to analyze the influence of the use of Besemah language communication and teacher involvement on improving language literacy in children at a public kindergarten in Pagar Alam City. This research is motivated by the phenomenon of declining Besemah language use among kindergarten children, despite this language being an important part of local identity. This study used quantitative methods and involved teachers at a public kindergarten in Pagar Alam City as research subjects. Data were collected through questionnaires, observations, and interviews, then analyzed using descriptive and inferential statistical techniques. The results indicate that the use of Besemah language communication and teacher involvement have a significant influence on improving children's language literacy. The use of Besemah language in learning helps children feel more confident and motivated to learn, while teacher involvement creates a conducive learning environment and supports children's language development. This study emphasizes the importance of preserving regional languages in early childhood education and the need for synergy between teachers, parents, and the community in supporting the development of children's language literacy.